A RANDOMIZED WAIT-LIST, PILOT DESIGN THESIS: Feasibility of the Web Accessible Population Pharmacokinetic Service-Hemophilia (WAPPS-Hemo) Tool in Severe Hemophilia Patients Undertaking Personalized Regimen Tailoring - Mussa, Joseph (My University, 2018)
A design pilot study proposed as a Canadian, multicenter, open-label, randomized waitlist clinical trial over the duration of six months to determine the success of running a full-scale RCT with the newly designed WAPPS-Hemo calculator in the Canadian Hemophilia community. The WAPPS-Hemo calculator is widely viewed as a beneficial tool to clinicians and patients and has the potential to optimize and tailor the prophylaxis regimen for hemophilia patients.
Keywords: hemophilia; wapps-hemo; prophylaxis